A three dimensional high-resolution reservoir model of Napo Formation in Oriente Basin, Ecuador, integrating sediment dynamic simulation and geostatistics. (December 2019) - Tang, Mingming; Lu, Shuangfang; Zhang, Kexin; Yin, Xiangdong; Ma, Huifang; Shi, Xian; Liu, Xueping; Chu, Changhong
Abstract: With the rapid development of computer hardware and software technology, 3D modeling technology of reservoirs has been widely applied in the exploration of oilfields. However, when modeling the reservoir with few wells, due to the absence of efficient constraints in interwell areas, the accuracy of the resulting 3D model is usually lacking. In this paper, we study the issue of model accuracy under the conditions of oil reservoir with few wells and propose a new 3D geological modeling method that is constrained by the multiple parameters based on sedimentary dynamics. We carry out a series of sediment dynamic simulation, by considering a number of key processes and parameters affecting the deposition of M1 member of Napo Formation in T-Oilfield, Oriente Basin, from 79.8 Ma to 76 Ma, to constrain the lithofacies and properties models. The proposed modeling method comprises two steps. First, the lithology distribution is obtained from a petrologic 3D model through the forward modeling of sedimentary processes. Second, geostatistical method is applied to build the reservoir geological model with the constraints of sedimentary dynamics, and logging information from work areas, the distribution of sedimentary characteristics by using a coordination Kriging modeling method. As a result, a high-degree fit is obtained between the actual characteristics of the strata and the reservoir model, with relative error of 4.6%, indicating future application of this method for geological modeling of reservoirs with few wells. Highlights: Sediment dynamic simulation could improve the reservoir modeling accuracy. The combination of sediment dynamic simulation and geostatistical modeling is a perfect way. Property distribution model is established under the constrain of sediment dynamic simulation results.